Investigation of Retinal Microvascular Findings in patients with Coronary Artery Disease - Doğan, Tolga; Serdar, Osman Akın; Topal, Naile Bolca; Yalçınbayır, Özgür (Journal of Cardiology and Cardiovascular Medicine, 2017)
Objectives: Retinal microvascular anomalies may be a marker for cardiovascular diseases. Our aim in this study was to investigate the utility of ocular fundoscopic examination as a noninvasive method in specifying the patients who carry a risk for coronary artery disease. Material and Method: Patients who were diagnosed with coronary artery disease by coronary angiography were included in our study. Bilateral fundoscopic examination was performed in these patients. Fundoscopic findings and risk factors for coronary artery disease were evaluated. Results: This study enrolled 100 patients (male: 72 (72%), mean age: 58.25±7.1) who were diagnosed with coronary artery disease by coronary angiography. Upon fundoscopic examination, 87% of the study population had atherosclerotic changes. Grade I atherosclerosis was found in 54% of the patients, grade II atherosclerosis was found in 32% of the patients and grade III atherosclerosis was found in 1% of the patients. Increased retinal tortuosity was present in 65% of the patients. Hollenhorst plaque was observed in 3 patients. Drusenoid bodies were observed with a statistically significantly higher rate in the patients who were not using clopidogrel compared to the patients who were using clopidogrel (p<0.001). Conclusions: Retinal findings are frequently found in patients with coronary artery disease. Therefore, fundoscopic examination is a noninvasive and feasible examination method which can be frequently used in the evaluation of cardiac functions.